Measuring psychological distress in older Aboriginal and Torres Strait Islanders Australians: a comparison of the K‐10 and K‐5. (12th October 2014) - McNamara, Bridgette J.; Banks, Emily; Gubhaju, Lina; Williamson, Anna; Joshy, Grace; Raphael, Beverley; Eades, Sandra J.
Abstract Objectives: To assess the cross‐cultural validity of two Kessler psychological distress scales (K‐10 and K‐5) by examining their measurement properties among older Aboriginal and Torres Strait Islanders and comparing them to those in non‐Aboriginal individuals from NSW Australia. Methods: Self‐reported questionnaire data from the 45 and Up Study for 1, 631 Aboriginal and 231, 774 non‐Aboriginal people were used to examine the factor structure, convergent validity, internal consistency and levels of missing data of K‐10 and K‐5. Results: We found excellent agreement in classification of distress of Aboriginal participants by K‐10 and K‐5 (weighted kappa=0.87), high internal consistency (Cronbach's alpha K‐10: 0.93, K‐5: 0.88), and factor structures consistent with those for the total Australian population. Convergent validity was evidenced by a strong graded relationship between the level of distress and the odds of: problems with daily activities due to emotional problems; current treatment for depression or anxiety; and poor quality of life. Conclusions and implications: K‐10 and K‐5 scales are promising tools for measuring psychological distress among Aboriginal and Torres Strait Islanders aged 45 and over in research and clinical settings.